IDEOLOGI FILM KARTUN ANIMASI ANAK (REFLEKSI FILOSOFIS ATAS PEDAGOGI TERSEMBUNYI DALAM DUNIA DISNEY) - Murtiningsih, Siti; Nugroho, Hastanti Widy (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractIdeologically, Disney animation cartoon films do not just represent pedagogical values in the traditional family culture, but also have conflicts between pedagogical values in generaltraditional family and Disneyâs natural characteristic as a bigcorporation that lives in the capital industry.We can see these conflicts clearly in a few Disneyâs box office films. âThe Lion Kingâ film shows a deep relation in nonsocialdemocracy, authority naturalization, hierarchy, unbalancedstructure, and full of patriarchy ideology values. âLittle Mermaidâ film has a strictly unbalanced gender. We can see that from Ariel, one of the characters in this film. Although, she is a pretty and active woman, but she is still on the position where she must obey the romanticism which is dominated by men. âCinderellaâ film shows a violence ideology in household, unbalanced gender, and dependency.Disney child animation cartoon film is able to reconstruct aâdifferent worldâ for children around the world which is not onlyfull of pedagogical values but also full of ideological values such as violence, unclearly values of life, and representation of an artificial world.Keywords: Ideology, Pedagogy, Child, Animation, Cartoon, Film,Disney